2023
DOI: 10.3389/fneur.2023.1292958
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive two-sample Mendelian randomization analysis of trigeminal neuralgia and modifiable risk factors

Xingrong Wei,
Hao Zhou,
Shuguang Zhang
et al.

Abstract: ObjectiveTo conduct a comprehensive search and causality study of potential modifiable risk factors for trigeminal neuralgia. To provide new ideas for subsequent treatment and management of patients with trigeminal neuralgia.MethodsData were obtained from large GWAS databases and then analyzed by Mendelian randomization analysis. The causal relationship between 36 potentially modifiable risk factors and trigeminal neuralgia was explored based on the results of the inverse variance weighting method(IVW). p &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Various small studies have found associations between TN and other conditions, such as anxiety, depression, autoimmune disorders, dementia, diabetes mellitus, and osteoporosis [30][31][32][33][34]. The association between TN and hypertension is equivocal.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Various small studies have found associations between TN and other conditions, such as anxiety, depression, autoimmune disorders, dementia, diabetes mellitus, and osteoporosis [30][31][32][33][34]. The association between TN and hypertension is equivocal.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%